A stakeholder perspective on public sector innovation: Linking the target groups of innovations to the inclusion of stakeholder ideas. (June 2023) - Boon, Jan; Wynen, Jan; Callens, Chesney
Public sector innovation scholarship has not yet systematically explored how the target context (or output phase) of innovations impacts the early phases of innovation processes. This study theorizes and tests whether innovating organizations are more sensitive to ideas from particular stakeholder groups depending on the target group of said innovation. Using a large-scale dataset from the Australian Public Service, the results show that innovations with external target groups are more likely to be built on ideas from external stakeholders (compared with internal stakeholders) and—within the group of internal stakeholders—on ideas from managers (compared with non-managerial employees). Practical and scholarly implications are discussed. Points for practitioners: Innovations benefit from the inclusion of internal and external stakeholder ideas, both substantively (appropriate knowledge leads to better end products) and symbolically (innovations need to be deemed legitimate, and receive support from the actors that will be primarily impacted by the innovation). Innovating organizations need to be aware of the perceptions of the stakeholders affected by the innovation, and properly sense, capture and translate the ideas of those stakeholders in the innovation process.